2020
DOI: 10.1161/jaha.119.014199
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin Methacryloyl Bioadhesive Improves Survival and Reduces Scar Burden in a Mouse Model of Myocardial Infarction

Abstract: Background Delivery of hydrogels to the heart is a promising strategy for mitigating the detrimental impact of myocardial infarction ( MI ). Challenges associated with the in vivo delivery of currently available hydrogels have limited clinical translation of this technology. Gelatin methacryloyl (Gel MA ) bioadhesive hydrogel could address many of the limitations of available hydrogels. The goal of this proof‐of‐concept study was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…For example, bio‐ionic liquids (e.g., based on choline) have been used to functionalize biomaterials, such as gelatin and polyethylene glycol, to yield biocompatible, conductive scaffolds that can promote healing of cardiac tissue in animal models. [ 403,404 ] Given their natural origin, bio‐ionic liquids likely offer better biocompatibility than other conductive materials. Furthermore, while biomaterial composites with carbon‐based materials or CPs are opaque, those with bio‐ionic liquids typically remain transparent, which is an advantage for imaging of cells laden throughout 3D scaffolds.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, bio‐ionic liquids (e.g., based on choline) have been used to functionalize biomaterials, such as gelatin and polyethylene glycol, to yield biocompatible, conductive scaffolds that can promote healing of cardiac tissue in animal models. [ 403,404 ] Given their natural origin, bio‐ionic liquids likely offer better biocompatibility than other conductive materials. Furthermore, while biomaterial composites with carbon‐based materials or CPs are opaque, those with bio‐ionic liquids typically remain transparent, which is an advantage for imaging of cells laden throughout 3D scaffolds.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…As NS/PCs cannot efficiently differentiate when cultured in a non-degradable, 3D hydrogel, biodegradability is needed. [389] For this reason, hydrogel biomaterials are often made with protease-degradable sites or from naturally biodegradable materials. For example, chitosan-graphene nanoparticles were disbursed within collagen I hydrogels, creating an enzymatically degradable, highly cytocompatible scaffold for NS/PCs.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Previous studies have demonstrated that the GelMA bioadhesive hydrogel reduced scar formation. 23 In this work, there are two main effects: (i) the injectable RSV@PLGA-GelMA hydrogel acts as a physical barrier to cover defects, and it prevents the scar from invading into the epidural area and (ii) simultaneously, RSV will be released from the hydrogel matrix; thus, a better anti-epidural fibrosis will be achieved. In this study, we further identify the type of collagen through picric−Sirius Red staining.…”
Section: 2mentioning
confidence: 99%
“…21,22 To the best of our knowledge, very few literature has explored the detailed therapeutic efficacy in managing epidural fibrosis utilizing GelMA hydrogels, although it was proved to have a positive effect on reducing cardiac fibrosis after myocardial infarction in a mouse model. 23 On the other hand, the effectiveness and efficiency of the singular hydrogel matrix strategy actually are limited; injecting anti-proliferation drug may achieve a better effect theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported hydrogel scaffolds prepared from various biocompatible polymeric materials that included N-isopropylacrylamide (NIPAAm), poly N-isopropylacrylamide (PNIPAAm), 2-hydroxyethyl methacrylate (HEMA), methacrylate polylactide (MAPLA), dextran (Dex), poly(ε-caprolactone) (PCL) and gelatine [ 79 , 80 , 81 ]. Poly (NIPAAm-co-HEMA-co-MAPLA) hydrogels [ 79 ] in an infarcted swine model, whereas Dex-PCL-HEMA/PNIPAAm (DPHP) hydrogels [ 80 ] and gelatine methacryloyl hydrogels [ 81 ] in infarcted rodents have also been shown to attenuate LV remodelling and improve cardiac function.…”
Section: Non-functionalised Acellular Scaffoldsmentioning
confidence: 99%